2012
DOI: 10.1517/13543776.2012.646261
|View full text |Cite
|
Sign up to set email alerts
|

Engineering endomorphin drugs: state of the art

Abstract: Importance of the field Although EM-1 (H-Tyr-Pro-Phe-Trp-NH2) and EM-2 (H-Tyr-Pro-Phe-Phe-NH2) are primarily considered agonists for the μ-opioid receptor (MOR), systematic alterations to specific residues provided antagonists and ligands with mixed μ/δ-opioid properties suitable for application to health related topics. Areas covered in this review This review attempts to succinctly provide insight on the development and bioactivity of endomorphin analogues during the past decade. Rational design approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…It has also been found in inflammatory tissue, implying that it may interact with immune cells. Astrocytes possess -opioid receptors, and endomorphins may play a role in the control of neuroinflammatory activity [99,100]. Morphine activates the -opioid receptor, which in turn activates the second messenger protein G i/o .…”
Section: Endomorphin-1 Stimulates the -Opioid Receptor And Na + /K + mentioning
confidence: 99%
“…It has also been found in inflammatory tissue, implying that it may interact with immune cells. Astrocytes possess -opioid receptors, and endomorphins may play a role in the control of neuroinflammatory activity [99,100]. Morphine activates the -opioid receptor, which in turn activates the second messenger protein G i/o .…”
Section: Endomorphin-1 Stimulates the -Opioid Receptor And Na + /K + mentioning
confidence: 99%
“…[ 2 ] In this context, potential of DNA vaccination for induction of specific cellular immune responses made it attractive for development of HCV vaccines if the amount of the responses elicited by such vaccination strategy could be enhanced. [ 3 4 ] Accordingly, results of the preceding attempts to utilize HCVcp for immunization (which has been considered as a superior immunogenic antigen) indicated that HCVcp is a rather weak immunogen when used in the context of DNA vaccine. [ 3 4 21 22 ] To overcome this shortcoming, formulations based on a mixture of DNA vaccine harboring HCVcp together with recombinant HCV core particles[ 6 ] or coadministration of IL-23 and GM-CSF were considered to enhance the immune responses toward HCV-core DNA vaccination regimen.…”
Section: Discussionmentioning
confidence: 99%
“…During prior years, great attempts and diverse strategies were employed to provide efficient vaccines against HCV infection by using different HCV antigens in various formulations and modalities such as recombinant protein (subunit), plasmid DNA, peptide, live vector-based and epitopic/polytopic vaccines. [ 2 3 ] Accumulated data from these previous studies suggested that cellular responses including HCV-specific cytotoxic T-lymphocytes (CTL) play a significant role in recovery of infected persons. In effect, CD8+ cell responses to viral epitopes accompanied with CD4+ helper activities and secretion of the Th1-type cytokines is shown to be efficient in HCV elimination, while the role of antibodies seems to be limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations